Risk Committee Attributes, Board Financial Expertise and The Market ‎Performance of Industrial Good Firms in Nigeria - Dagunduro, Muyiwa Emmanuel; Falana, Gbenga Ayodele; Omodara, Olasehinde Vincent; Fagbomedo, Bukola Ibilola; Aluko, Adebimpe Funmilayo; Olufemi, Simeon Opeyemi; Ogunleye, Akinyemi Wumi; Osaloni , Bankole Ojo (International Journal of Accounting and Economics Studies, 2025)
The study investigated how the risk management committee (RMC) attributes—size, independence, diligence, and financial expertise — influence the market performance (as quantified by the Q of Tobin) of listed industrial goods in Nigeria. The present research design was ex-post facto ‎, utilizing secondary data on 13 listed firms in Nigeria that manufacture industrial goods. The sample was of all 13 firms using a census sampling ‎method. The data used was back through the 14-year period between 2010 to 2023. Grasping ‎the use of descriptive as well as inferential statistics. The empirical test showed a significant ‎positive effect of size and independence of RMCs as having an effect that would improve the ‎quality of governance and investor confidence in the wider and more independent committee. On ‎the contrary, RMC diligence and financial knowledge proved to have major adverse effects, ‎meaning that too many gatherings and uncoordinated professional knowledge can slow down firm ‎valuation. Also, financial skills on the board play the negative moderating role, showing the ‎existence of overlaps in roles or inefficient governance when technical authority is ‎concentrated. This study established that although risk committee size and independence improve ‎market performance, undue diligence and expertise about financial matters are displayed by the ‎committee. The research advises firms to strive to have a balanced size of RMC, which will ‎promote healthy diversity of opinion without being inefficient‎.